2022
DOI: 10.1111/pbi.13813
|View full text |Cite
|
Sign up to set email alerts
|

Plant‐based expression and characterization of SARS‐CoV‐2 virus‐like particles presenting a native spike protein

Abstract: Summary We have investigated the use of transient expression to produce virus‐like particles (VLPs) of severe acute respiratory syndrome coronavirus 2, the causative agent of COVID‐19, in Nicotiana benthamiana . Expression of a native form of the spike (S) protein, either alone or in combination with the envelope (E) and membrane (M) proteins, all of which were directed to the plant membranes via their native sequences, was assessed. The full‐length S protein, together with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 49 publications
2
23
0
Order By: Relevance
“…Samples were added to the sample buffer without the presence of reducing agents and were not boiled, to preserve disulfide bonds. We firstly detected the trimer in the cell extract, similarly to what has been reported in N. benthamiana leaves (Jung et al, 2022). WB analysis (Figure 7A) detected two bands in the HEK-S sample, corresponding to the glycosylated monomer, around 180 kDa, and a higher molecular weight band that may correspond to the trimer.…”
Section: Spike Protein Was Successfully Produced In Cell Cultures Of ...supporting
confidence: 76%
“…Samples were added to the sample buffer without the presence of reducing agents and were not boiled, to preserve disulfide bonds. We firstly detected the trimer in the cell extract, similarly to what has been reported in N. benthamiana leaves (Jung et al, 2022). WB analysis (Figure 7A) detected two bands in the HEK-S sample, corresponding to the glycosylated monomer, around 180 kDa, and a higher molecular weight band that may correspond to the trimer.…”
Section: Spike Protein Was Successfully Produced In Cell Cultures Of ...supporting
confidence: 76%
“…The SARS-CoV-2 S protein produced in N. benthamiana has a molecular weight of about 140 kDa in reducing conditions [17]. Post-translational modifications of this recombinant protein were investigated by mass spectrometry analysis of peptides generated by endoprotease digestions.…”
Section: Post-translational Modifications Of the Sars-cov-2 S Protein...mentioning
confidence: 99%
“…VLPs containing the S protein from SARS-CoV-2 isolate Wuhan-Hu-1 (NC_045512.2) were expressed in N. benthamiana and purified as previously described [17]. As determined by ELISA measurement of the amount of S protein in the VLP sample, 50 µg of SARS-CoV-2 S protein were separated by electrophoresis on an 8% (w/v) SDS-PAGE gel.…”
Section: Endoprotease Digestionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kentucky BioProcessing is developing a recombinant subunit RBD-based vaccine in plants and has already started phase 1–2 clinical trials (NCT04473690). In other studies, it was shown that simultaneous transient expression of envelop (E), membrane (M), and S proteins in Nicotiana benthamiana resulted in VLP formation [ 47 , 48 ]; as well as the co-expression of M, E and nucleocapsid (P) [ 49 ].…”
Section: Introductionmentioning
confidence: 99%